University Students’ vs. Lay People’s Perspectives on Organ Donation and Improving Health Communication in Poland - Boratyński, Wojciech; Bączek, Grażyna; Dyzmann-Sroka, Agnieszka; Jędrzejczak, Agnieszka; Kielan, Aleksandra; Mularczyk-Tomczewska, Paulina; Nowak, Ewa; Steć, Małgorzata; Szynkiewicz, Mariusz (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2018)
Given that organ transplant is a standard medical technology admitted in medical practice, and taking into consideration that Polish transplantology is regarded among the most advanced in the world one should expect to find similarly high levels of acceptance in interviewees asked for their opinion on vital organ transplantation and their willingness to donate a paired organ ex vivo, or a vital organ ex mortuo in order to rescue the life of a recipient with a missing vital organ. The paper presents research build on the societal assessment of vital organ donation and transplant policies in Poland with the focus on students. Data have been collected at three different universities (Boratyński et al., Questionnaire on the Bases of Transplantation Medicine 2016/7). Various assessments concerning a vital organ donation have been observed. The authors discuss educational factors contributing to these variety including factual knowledge and ethical issues.
Keywords: organ donation; societal assessment; transplant policies in Poland; promoting decision making; health communication and discourse in university education